Relationship Between Stock Market and Economy: Empirical Evidence from India - Mayur, Manas (Asian Journal of Empirical Research, 2017)
The objective of this paper is to determine if the macroeconomic variables affect the Indian stock market. Sensex was chosen as the indicator of the Indian stock market. The study reveals that the Indian stock market has a positive relationship with macroeconomic variables like the wholesale price index, index of industrial production and short term interest rate and a negative relationship with oil prices and exchange rates. The paper provides a practical insight to the academicians to understand the various models used in the study. It also contradicts some of the theories and provides reasons why there are contradictory results.